Pengaruh Kualitas Pelayanan Terhadap Kepuasan Tamu Hotel Benua Mas Pontianak - Ahie, Simon (Jurnal Ekonomi STIEP ( JES ), 2019)
This reseach was carried out on the company Benua Mas Hotel Pontianak. Common problems in thisstudy are â€œHow Does the Quality of Service Affect Hotel Guests Benua Mas Pontianakâ€. Reseachers usedqualitative desciptive methods. Data analysis techniques used are multiple linear regression, the researchtechnique in this study is in form documentation techniques by collection data from Benua Mas Hotel Pontianak.This study examines the quality of service consisting of five dimensions that is physical evidance, reliability,responsiveness, guarantee and empathy, and customer satisfaction on Benua Mas Hotel Pontianak. Based on themethod of determining the sample, the sample used was 30 respondents.Based on the results of simultaneous tes/ F test can be seen that independent variables have influence tothe dependent variable. From the results of the analysis carried out indicate that service quality service consistingof five dimensions, namely physical evidance, reliability, responsiveness, guarantee and empathy, simultaneouslyaffect customer satisfaction Benua Mas Hotel Pontianak.Physical evidance variables affect hotel customer satisfaction Benua Mas Pontianak, while the reliabilityvariable, responsiveness variable, guarantee variables and empathy variables does not affect hotel customersatisfaction Benua Mas Pontianak.